2015
DOI: 10.12659/msm.895209
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Remifentanil and Dexmedetomidine in General Anesthesia for Cesarean Delivery

Abstract: BackgroundUse of remifentanil and dexmedetomidine in general anesthesia for cesarean section have been described. This study was designed to evaluate the effects of remifentanil and dexmedetomidine on maternal hemodynamics and bispectral index, and neonatal outcomes in elective caesarean delivery.Material/MethodsForty-four women undergoing elective cesarean delivery with ASA I or II and term or near-term singleton pregnancies were randomly assigned to receive remifentanil at a loading dose of 2 μg/kg over 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 37 publications
3
42
0
1
Order By: Relevance
“…While group R showed no significant changes all over the surgery in the hemodynamics. These desirable effects of remifentanil on hemodynamic stability has been shown in previous studies using different doses of remifentanil [24][25][26][27].…”
Section: Discussionsupporting
confidence: 62%
“…While group R showed no significant changes all over the surgery in the hemodynamics. These desirable effects of remifentanil on hemodynamic stability has been shown in previous studies using different doses of remifentanil [24][25][26][27].…”
Section: Discussionsupporting
confidence: 62%
“…The dose and intervention of DEX we chose was similar to those used in previous research. 16,30 Dexmedetomidine can be safely used in adults, and the dose used in this study is completely acceptable. 31 There was no significant difference between the DEX group and the standard care group in drugrelated adverse events (such as severe bradycardia or fluctuation in blood pressure), which is in agreement with other reports.…”
Section: Discussionmentioning
confidence: 93%
“…1 Both fentanyl and dexmedetomidine is known to decrease the manifestation of sympathetic nervous system activation. 1,[4][5][6][7][8][9][10][11][12][13] In the present study, heart rate significantly decreased in the dexmedetomidine group when compared to fentanyl group immediately after study drug infusion and there was statistically significant reduction in heart rate for up to 5 min after intubation in both the groups. Although heart rate increased after intubation in both the groups, the magnitude was lower in the Dexmedetomidine group.…”
Section: Discussionmentioning
confidence: 64%
“…10 Dexmedetomidine has also been compared to remifentanil, esmolol and lignocaine. 5,11,12,13 In these randomized studies, dexmedetomidine was found to be of similar efficacy to remifentanil albeit with less potentials for respiratory depression, whereas it was superior compared to esmolol or lignocaine. 11,12,13 Bradycardia was observed in one patient each in the study by Gunalan et al and Kharwar et al 6,7 No such adverse effect was observed in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation